Barrier coverage in wireless sensor networks with adjustable sensing ranges. (20th March 2014) - Deng, Xianjun; Wang, Bang; Wang, Changqing; Liu, Wenyu
In this paper, we study the barrier lifetime maximisation (BLM) and barrier gap mending (BGM) problem in a sensor network, where sensors can choose to use different sensing ranges when constructing a sensor barrier. In the BLM problem, for small–scale sensor networks, we propose a linear programming optimisation method. For large–scale sensor networks, we propose two distributed heuristics to select a next node to construct barriers. Simulation results show that compared with the randomised one, the greedy scheme can achieve longer lifetime. In the BGM problem, we study how to efficiently mend barrier gaps in a hybrid sensor network consisting of both stationary and mobile sensors. We propose two gap mending schemes: the min–max scheme to minimise the maximal energy consumption to move sensors, and the max–lifetime scheme to maximise the lifetime of barrier coverage after mending all gaps. Simulation results show that the min–max scheme can achieve a lower maximal moving distance and the max–lifetime scheme can efficiently extend the barrier lifetime.